A multidimensional view of the influence of entrepreneurial orientation on women business success: A conceptual proposition - Hashimu, Salaudeen Nuraini; Bakar, Muhammad Shukri; Mahmood, Rosli (2017)
A number of studies have established relationship between entrepreneurial orientation (EO) and business success. However, there are dearth of studies that have considered the relationship between individual entrepreneurial orientation (IEO) and entrepreneur’s business success.Even if there exist any of such studies, only few of them have considered the individual influence of its dimensions on entrepreneurs’ business success.This paper therefore, proposes the trinomial effects of individual entrepreneurial orientation (IEO) on women business success.